Evaluation of alternative spatial models of party competition across voters` ideological positions: empirical evidence from Turkiye = Ocena alternatywnych modeli przestrzennych konkurencji między partiami w kontekście ideologicznych pozycji wyborców: dowody empiryczne z Turcji - Inan, Murat; Arikan-Akdag, Gül (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This research aims to evaluate the appropriateness of proximity and directional models of voting among voters occupying different ideological positions on the ideological spectrum. The proximity model suggests that voters vote for parties or candidates whose ideological or issue positions are the closest to their own. In contrast, the directional model proposes that voters vote favor parties that are on their side of the ideological or issue position, more but not too extreme than their positions.
Keywords: zachowania wyborcze; alternatywne modele przestrzenne konkurencji między partiami; ideologia polityczna; Turcja - polityka; voting behavior; alternative spatial models of party competition; political ideology; Turkish politics